The tooth size discrepancy among orthodontic patients and normal occlusion individuals from Saudi Arabia: A three-dimensional scan analysis of diagnostic casts - Abdulaziz Abdullah Alshahrani; Ibrahim Alshahrani; Mohamed Khaled Addas; Sharaz Shaik; Faris Mohammed Binhomran; Jaber AlQahtani (Wolters Kluwer Medknow Publications, 2020)
Background/Purpose: Tooth size discrepancy is one of the causative factors of malocclusion. This study aimed to establish the TDS among various malocclusion classes and normal occlusion subjects in a Southern Saudi population. Materials and Methods: The study casts of orthodontic patients from Southern Saudi Arabia (mean age: 19.6 years ± 2.45; n = 120) were randomly selected and grouped into eight equal classes based on Angle's classification and gender. An additional 30 study casts, devoid of malocclusion, having excellent intercuspation and class I occlusion, were grouped into two controls (n = 15) based on gender. The study casts were three-dimensional scanned to measure mesiodistal widths of all the teeth. The calculated anterior ratios (AR) and overall ratio (OR) were statistically analyzed with analysis of variance and t-tests. Results: There were no significant differences in "OR" and "AR" between the genders (P > 0.05) and among the malocclusion and control subgroups (P > 0.05). The mean "OR" (92.01 ± 0.18) and "AR" (78.60 ± 0.27) of the malocclusion group were significantly higher than that of Bolton's ratios (P > 0.05). The "AR" of the control group was significantly higher than Bolton's standards (P = 0.048). However, "OR" was no different (P = 0.105). Malocclusion patients displayed a discrepancy (±2 standard deviation) in "AR" of 22.5% and 'OR' of 6.7% from Bolton's mean (BM). Similarly, the control group displayed a discrepancy in "AR" of 20% and "OR" of 10% from BM. Conclusion: The mean "OR" and "AR" of the Southern Saudi population showed no sexual dimorphism and no significant difference among various malocclusion and control subgroups. The "AR" of the malocclusion and control subgroups did not comply with Bolton's standards.